Mitochondrial priming in therapy-induced senescence: implications for CAR-T/NK immunosenolytic therapy - Menendez, Javier A.; Lupu, Ruth; Martin-Castillo, Begoña; Sardanyés, Josep; Alarcón, Tomás; Verdura, Sara; Cuyàs, Elisabet (Frontiers in Immunology, 2025)
Therapy-induced senescence (TIS) generates an immunogenic state in cancer cells by altering how they present antigens, produce cytokines, and organize their surfaceome. TIS can be exploited for therapeutic purposes using “immunosenolytic” strategies, including adoptive cellular therapies such as chimeric antigen receptor (CAR)-engineered T and natural killer (NK) cells. A frequently overlooked barrier may limit the success of these living drugs: mitochondrial apoptotic priming in the target TIS cancer cells. Contrary to the prevailing dogma, recent assessments of mitochondrial apoptotic signaling via BH3 profiling (a functional assay measuring proximity to the mitochondrial apoptotic threshold and identifying BCL-2 family dependencies) have revealed that TIS cancer cells are globally less primed for apoptosis than their proliferating precursors. TIS cancer cells exhibit a conserved, druggable dependence on specific members of the BCL-2 family for survival. Interestingly, the pre-existing priming and anti-apoptotic addictions of parental, non-senescent cells, are retained upon induction of senescence. This suggests an “inherited” mitochondrial memory that may predict the (immuno)senolytic responsiveness of TIS cancer cells. BH3 profiling could help to personalize CAR-based immunosenolytic therapy according to apoptotic readiness across pre- and post-TIS states. This companion diagnostic could inform the rational use of BH3 mimetics in combination with CARs and guide the engineering of precision immunosenolytic interventions such as “armored” CAR-T/NK cells neutralizing specific anti-apoptotic dependencies at the effector-target interface. This perspective reframes mitochondria as predictive checkpoints that can be monitored and targeted to enable TIS cancer cells to respond precisely and durably to adoptive CAR-T/NK immunotherapy within “one-two punch” senogenic-immunosenolytic designs.